Specific responses of cuckoo hosts to different alarm signals according to breeding stage: a test of the offspring value hypothesis. Issue 6 (16th May 2020) - Wang, Jiaojiao; Yang, Canchao
Abstract: The selective pressure exerted by avian brood parasites forces their hosts to evolve specific defense strategies. When subject to brood parasite attack, avian hosts will often emit alarm calls. To date, few studies have examined whether and how host responses to different alarm calls indicative of different enemies vary with the host's breeding stage. We carried out alarm call playback experiments during both the egg and nestling stages of the oriental reed warbler Acrocephalus orientalis, a host of the common cuckoo Cuculus canorus . The playback exemplars were selected from recorded alarm calls of the warbler to the presence of common cuckoos, sparrowhawks Accipiter nisus, and oriental turtle doves Streptopelia orientalis, which represented brood parasite, predator, and harmless control, respectively. The results showed that the oriental reed warblers did not discriminate alarm calls issued to different intruder types, but the intensity of the response was significantly higher in the nestling stage than in the egg stage. Attack behavior related to sparrowhawk alarm calls was absent in the egg stage, but aggressive behavior increased dramatically and exceeded the attack frequency in response to the cuckoo alarm call in the nestling stage, implying a shift in the tradeoff between the parents' own survival and the loss of offspring. Alarm calls attracted a larger number of conspecifics than members of other species. In general, the oriental reed warbler had consistently stronger responses to different alarm calls in the nestling stage than in the egg stage, supporting the offspring value hypothesis.